Achieving Success with the Research Domain Criteria (RDoC): Going beyond the Matrix - Iacono, William G. (Psychophysiology, 2016)
Achieving Research Domain Criteria (RDoC) goals depends in part on how well scientists can grasp its principles and execute studies within its framework. Ford provides an exemplary illustration of a research program that aligns with RDoC guidelines. The future success of RDoC depends not just on research like that of Ford and colleagues. RDoC also must inspire the development of reliable neurobehavioral measures with demonstrable clinical validity that produce replicable findings leading to the establishment of neurocircuit-based behavioral dimensions that inform clinical work. Large samples not typically attainable in a clinical neuroscience laboratory or easily imagined within the confines of the RDoC matrix will be required if RDoC is to develop the insights and tools needed to establish incremental value over the DSM. Innovation that goes beyond reliance on the RDoC matrix and measures of neurocircuitry can help facilitate achievement of RDoC's goal of developing a science of psychopathology based on neurobiological systems.